Biology and Feeding Potential of Cheilomenes sexmaculata Fabricius (Coleoptera: CoccineIlidae) on Mustard Aphid - Singh, Y P; Meghwal, H P; Singh, S P (Annals of Arid Zone, 2016)
The biology and feeding potential of Cheilomenes sexmaculala Fabricius was studied in the laboratory at 27±2°C and 70±5% relative humidity on mustard aphid, Lipaphis erysimi Kaltenbach at National Research Centre on Rapeseed- Mustard, Bharatpur during 2006-07 in two sets of observations. The pooled mean fecundity was recorded as 294.80±18.79 eggs per female. The pooled mean ovipositional period, incubation period, larval period, pupal period, total developmental period (egg to adult) and adult longevity were recorded as 27.55±1.33, 2.68±0.12, 11.08± 0.21, 4.48±0.16, 18.24±0.49 and 92.25±1.61 days, respectively. The pooled mean feeding potential of grub and adult was 26.82±0.59 and 47.13±1.75 aphids per day per individual, respectively. Key words: Biology, Cheilomenes sexmaculala, feeding potential, Lipaphis erysimi, mustard aphid.